Technology Acceptance Model in using E-learning on Early Childhood Teacher Education Programs student during pandemic - Tri Endang Jatmikowati; Angraeny Unedia Rachman; Asti Bhawika Adwitiya (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
During the COVID-19 pandemic many education institutions implement e-learning as a replacement of traditional face to face teaching and learning activities. This situation forced students and teachers to adapt to the new normal of teaching and learning activity. This study aimed to examine the determinant factors of behavioral intention of using e-learning associated with the Technology Acceptance Model (TAM) for early childhood teacher education students. The factors included in the model are perceived ease of use, perceived usefulness, attitude, behavioral intention, self-efficacy, subjective norm, and system accessibility. Partial Least Square-Structural Equation Model (PLS-SEM) technique was employed with SmartPLS as a computational software. Using samples students in Early Childhood Teacher Education Program in Muhammadiyah University of Jember Indonesia, this study result that perceived usefulness affects behavioral intention directly while self-efficacy affect behavioral intention directly and indirectly through perceived usefulness.